Effect of Incorporation of Glutinous Rice Flour on Quality of Duck Meat Salamis - Jebin, Nashrin; Laskar, S.K.; Hazarika, M.; Nath, D.R.; Rahman, Z.; Chavhan , D.M. (Journal of Meat Science, 2012)
This study was carried out with the aim to develop duck meat salamis with incorporation of glutinous rice flour. Four different formulations viz. Control, A, B and C were prepared by adding decreasing levels of duck fat (15, 10, 8 and 5 % ) and increasing levels of glutinous rice flour (0, 5, 7 and 10 %), respectively and subjecting to certain quality evaluation for emulsion stability, cooking loss, proximate composition and organoleptic evaluation. Emulsion stability was found to be significantly (P < 0.01) higher in formulation C as compared to that of control. Proximate composition of salamis revealed a significant (P < 0.01) decrease in the per cent moisture content from control (65.27 ± 0.29) to formulation C (65.04 ± 0.23). There was a significant (P < 0.01) decrease in the per cent ether extract from control (16.67 ± 0.20) to formulation C (11.98 ± 0.23), however, a significant rise (P < 0.05) in the per cent crude protein content from control (14.36 ± 0.19) to the formulation C (14.41 ± 0.27) was observed. The overall acceptability of formulation B (7.75 ± 0.19) was significantly (P < 0.01) higher as compared to the Control (7.23 ± 0.16), A (7.41 ± 0.17) and C (7.54 ± 0.18). From the above study, it can be concluded that suitable fat reduced duck meat salamis can be prepared successfully and that the best product can be obtained by incorporation of 8 per cent duck fat and 7 per cent glutinous rice flour.